Automated Reasoning with Analytic Tableaux and Related Methods : 24th International Conference, TABLEAUX 2015, Wroclaw, Poland, September 21-24, 2015, Proceedings - De Nivelle, Hans.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 24th International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2015, held in Wroclaw, Poland, in September 2015. The 19 full papers and 2 papers presented in this volume were carefully reviewed and selected from 34 submissions. They are organized in topical sections named: tableaux calculi; sequent calculus; resolution; other calculi; and applications. .
Keywords: Artificial intelligence; Computer science; Software engineering; Computational complexity; Logic design; Artificial Intelligence; Mathematical Logic and Formal Languages; Programming Techniques; Software Engineering; Discrete Mathematics in Computer Science; Logics and Meanings of Programs